O fornecimento de cana-de-açúcar para usina e a diversificação produtiva no assentamento Ibitiúva no município de Pitangueiras - SP - Amorim, Fernando Rodrigues de (2013)
This study aimed at analyzing the productive dynamics of the Ibitiúva Rural Settlement (Ibitiúva State Settlement) located in the municipality of Pitangueiras, São Paulo, Brazil, and characterized by a production system based on supplying sugar cane to the processing station from the majority of the settled producers. The work presented the following specific objectives in its investigation: causes which lead the producers to leasing their lands to supply sugar cane to the processing station; history of the producers lives and their perspectives regarding the future of this sugar cane supplying system; alternatives for new sustainable production arrangements for the settled, meeting the environmental, social and economic criteria, from an alternative system based on the diversity of rural production in contrast to sugar cane monoculture, grounded on associative activities between the associates, with the objective of increasing their autonomy in relation to other power instances; insufficiency of municipal public politics focused on the rural settlements by the municipality of Pitangueiras. For a better understanding of this system based on supplying agricultural raw material by the settled for a sugar producing agroindustrial unit, we performed an analysis of general economic context, comprehending the following subjects: the Complexo Rural ao Agroindustrial; Green Revolution; the Agrarian Reform and the formation of settlements in Brazil; Agricultural, Rural and Local Development; and Economic Politics destined to Agriculture. Subsequently, the study analyzed the main characteristics of the Ibitiúva Rural Settlement, highlighting its formation, origin of the settled and its socio-economic characteristics. Furthermore, the study analyzed the conditions in which the food production activities for self-consumption and commercialization are performed, which are secondary in regard to the planting system for supplying the processing station. Finally, the research investigated the main characteristics of this supplying system, highlighting its environmental, social and economic limitations through the contrast represented by their debatable monetary gains for the settled suppliers in contrast to an alternative of agriculture based on food diversity and associative production and commertialization structures.